2015
DOI: 10.1002/ejic.201500882
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a Naphthaldiimide Substituent at the Diimine Ligand on the Photophysics and Reverse Saturable Absorption of PtII Diimine Complexes and Cationic IrIII Complexes

Abstract: Two PtII complexes containing benzothiazolylfluorenyl (BTF) acetylide ligands and different diimine (NN) ligands [NN = 1,10‐phenanthroline (1), 5‐naphthaldiimide–1,10‐phenanthroline (2)] and two heteroleptic cationic IrIII complexes containing the 5‐naphthaldiimide–1,10‐phenanthroline ligand and different phenylpyridine (CN) ligands [CN = 2‐phenylpyridine (3), 2‐{3‐[7‐(benzothiazol‐2‐yl)fluoren‐2‐yl]phenyl}pyridine (4)] were synthesized and characterized. The influence of naphthaldiimide (NDI) attached to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 65 publications
1
12
0
Order By: Relevance
“…The chosen DFT‐based methodology represents one of the currently most popular density functionals and basis sets, which previously has shown good agreement with UV/Vis experimental data for various Pt(II), Ru(II) and Ir(III) complexes . The validity of various hybrid DFT functionals with different portions of Hartree–Fock (HF) exchange has been widely tested for description of geometries and optical properties of various transition metal complexes , .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The chosen DFT‐based methodology represents one of the currently most popular density functionals and basis sets, which previously has shown good agreement with UV/Vis experimental data for various Pt(II), Ru(II) and Ir(III) complexes . The validity of various hybrid DFT functionals with different portions of Hartree–Fock (HF) exchange has been widely tested for description of geometries and optical properties of various transition metal complexes , .…”
Section: Methodsmentioning
confidence: 99%
“…In order to facilitate RSA of nanosecond laser pulses, an absorber should have a weak ground‐state absorption to populate the excited states, but long–lived triplet excited states, large triplet‐triplet excited‐state absorption coefficients, and a high quantum yield for triplet excited‐state formation. In recent years, the RSA of heavy transition‐metal complexes, such as octahedral Ir(III) complexes, have been extensively explored by our group, , , , and other groups, because these complexes displayed the aforementioned characteristics that well match the requirements for RSA. In addition, by structural modifications, both the ground‐ and excited‐state properties can be readily tuned in these complexes for optimization of the RSA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strong spin–orbit coupling (SOC) caused by the central Ir­(III) atom can promote the triplet to ground state radiative transition, leading to high phosphorescence quantum yields at room temperature. This unique character makes Ir­(III) complexes promising candidates for applications in organic light-emitting devices, organic light-emitting electrochemical transistors, low-power upconversion, photocatalysts, luminescent biological labeling, nonlinear optics, and ion detection …”
Section: Introductionmentioning
confidence: 99%
“…Also, recently, some of us reported that a “phenylalkynyl-Ru” moiety behaves as a good donor in various NLO-efficient push–pull architectures bearing an acceptor group such as methyl cyanoacrylate or 2,1,3-benzothiadiazole . In addition, the photophysical properties of various Pt­(II) acetylide complexes have been investigated and some of them are characterized by interesting third-order NLO properties such as two-photon absorption cross sections or strong reverse saturable absorption . Also, some terpyridyl and cyclometalated (dipyridyl)­benzene platinum­(II) complexes with a phenylalkynyl ancillary ligand are characterized by a high, second-order NLO response, as determined by the hyper-Rayleigh scattering and EFISH techniques, where the “phenylalkynyl-Pt” moiety and the tridentate ligand act as a donor and an acceptor, respectively …”
Section: Introductionmentioning
confidence: 99%